Injury among children and young adults with epilepsy - Prasad, Vibhore; Kendrick, Denise; Sayal, Kapil; Thomas, Sara L.; West, Joe (American Academy of Pediatrics, 2014)
OBJECTIVE: To investigate whether children and young adults with epilepsy are at a greater risk of fracture, thermal injury, or poisoning than those without. METHODS: A cohort study was conducted by using the Clinical Practice Research Datalink (1987–2009), a longitudinal database containing primary care records. A total of 11 934 people with epilepsy and 46 598 without, aged between 1 and 24 years at diagnosis, were followed for a median (interquartile range) of 2.6 (0.8–5.9) years. The risk of fractures (including long bone fractures), thermal injuries, and poisonings (including medicinal and nonmedicinal poisonings) was estimated. RESULTS: Adjusting for age, gender, Strategic Health Authority region, deprivation, and calendar year at study entry (and, for medicinal poisonings, behavior disorder), people with epilepsy had an 18% increase in risk of fracture (hazard ratio [HR] = 1.18; 95% confidence interval [CI], 1.09–1.27), a 23% increase in risk of long bone fracture (HR = 1.23; 95% CI, 1.10–1.38), a 49% increase in risk of thermal injury (HR = 1.49; 95% CI, 1.27–1.75), and more than twice the risk of poisoning (HR = 2.47; 95% CI, 2.15–2.84), which was limited to poisoning from medicinal products (medicinal HR = 2.54; 95% CI, 2.16–2.99; nonmedicinal HR = 0.96; 95% CI, 0.61–1.52). CONCLUSIONS: Children and young adults with epilepsy are at a greater risk of fracture, thermal injury, and poisoning than those without. The greatest risk is from medicinal poisonings. Doctors and other health care professionals should provide injury and poison prevention advice at diagnosis and epilepsy reviews.